Low-Intensity Focused Ultrasound-Augmented Multifunctional Nanoparticles for Integrating Ultrasound Imaging and Synergistic Therapy of Metastatic Breast Cancer - Qian Zhang; Wen Wang; Hongyuan Shen; Hongyu Tao; Yating Wu; Liyuan Ma; Guangfei Yang; Ruijiao Chang; Jiaxing Wang; Hanfei Zhang; Chenyu Wang; Furong Zhang; et al. (Nanoscale Research Letters, 2021)
Abstract The metastasis of breast cancer is believed to have a negative effect on its prognosis. Benefiting from the remarkable deep-penetrating and noninvasive characteristics, sonodynamic therapy (SDT) demonstrates a whole series of potential leading to cancer treatment. To relieve the limitation of monotherapy, a multifunctional nanoplatform has been explored to realize the synergistic treatment efficiency. Herein, we establish a novel multifunctional nano-system which encapsulates chlorin e6 (Ce6, for SDT), perfluoropentane (PFP, for ultrasound imaging), and docetaxel (DTX, for chemotherapy) in a well-designed PLGA core–shell structure. The synergistic Ce6/PFP/DTX/PLGA nanoparticles (CPDP NPs) featured with excellent biocompatibility and stability primarily enable its further application. Upon low-intensity focused ultrasound (LIFU) irradiation, the enhanced ultrasound imaging could be revealed both in vitro and in vivo. More importantly, combined with LIFU, the nanoparticles exhibit intriguing antitumor capability through Ce6-induced cytotoxic reactive oxygen species as well as DTX releasing to generate a concerted therapeutic efficiency. Furthermore, this treating strategy actives a strong anti-metastasis capability by which lung metastatic nodules have been significantly reduced. The results indicate that the SDT-oriented nanoplatform combined with chemotherapy could be provided as a promising approach in elevating effective synergistic therapy and suppressing lung metastasis of breast cancer.